The effects of a self-talk intervention on a divided attention golf task under conditions of ego-depletion - Kooijman, Jelle (2018)
Previous research has indicated a negative effect of ego-depletion on various sport performance tasks. However, a recent study using a non-sport attention task indicated that the use of self-talk could partly counteract the negative effects of ego-depletion. The next step in this line of research is to extend the task to a real sport task in a controlled lab environment. Therefore, the aim of this study is to examine the effects of a self-talk intervention on a divided attention golf task under a state of ego-depletion. A mixed between- (experimental vs. control group) and within- (before vs. after manipulation) design was used. Participants completed a baseline performance measure, followed by a training period in which the experimental group practiced using self-talk. Subsequently, both groups received an induction of ego-depletion. Finally, all groups completed a final divided attention golf-task. Results showed that the experimental group significantly increased their performance on the final measurement compared to the baseline measurement while the control group did not increase their performance. The findings suggest that the self-talk intervention successfully counteracted the effects of a state of ego-depletion on this lab-based sport task.